Childhood-Onset Systemic Lupus Erythematosus: How Is It Associated with Breastfeeding and Mode of Delivery? - Tahghighi, Fatemeh; Sadeghi, Banafsheh; Rayzan, Elham; Shariat, Mamak; Nayeri, Fatemeh; Ziaee, Vahid (Journal of Child Science, 2020)
Breast milk is a rich source of infants' nutrition and also known to be a source of immune-enhancing molecules. The perinatal factors might have long-term effects on the immune system and also, breastfeeding may have an important role. Systemic lupus erythematosus (SLE) is a multisystemic autoimmune disease that leads to various organ damages. This idiopathic disease is characterized by high levels of autoantibodies in the circulation. In this case–control study, we have evaluated the association between the breastfeeding and mode of delivery and SLE incidence. In this case–control study, SLE cases were identified in Children's Medical Center and Imam Khomeini Hospital Complex between 2011 and 2017. The control group was chosen from the schools of Tehran and Sari cities. The questionnaires were completed by one of the parents. Seventy-nine cases and 301 controls were included. There was no association among breastfeeding, duration of breastfeeding or exclusive breastfeeding and SLE, the age of diagnosis, or its major organ involvements (p > 0.05). The cesarean section (C-section) method was significantly associated with higher disease incidence (p < 0.005). The feeding method during infancy had no significant impact on SLE incidence and onset, while the C-section method increased the incident rate.
Keywords: breastfeeding; exclusive breastfeeding; systemic lupus erythematous